USAGE OF THERMOGRAPHY AS INDIRECT NON-INVASIVE METHOD OF EVALUATION OF PHYSICAL EFFICIENCY. PILOT STUDY - Jakub Grzegorz Adamczyk; Mariusz Mastej; Dariusz Boguszewski; Dariusz Białoszewski (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Introduction. One of main features deciding on functional abilities and agility of a man is his conative efficiency. The aim of the study was to determine the influence of physical effort on changes of skin temperature of each body areas and the analysis of dependence between the body temperature and the level of maximum absorption of oxygen (VO2max). Material and methods: The study group consisted of 7 women at about average age of 23.86 (+-0.69) years. All participants of the study were healthy, did not have overweight nor chronic illnesses. They also did not do sport professionally. During the research each participant performed the effort in the form of 6 - 8-minute-long step Astrand - Rhyming test and then 10-12-minute-long run on the athletic track. Before and after the effort the women were examined by means of thermo visual cameras (temperature in front and back of the body). In the moment of effort ending studied persons had heart rate measured with heart rate monitor. Results. Statistically non-exchangeable temperature reduction of body surface on thighs, forearms, arms, trunk (both in front as well as the back) and behind shins was observed during the study. The greatest drop of about -1.13 В°C, appeared behind shoulders, least, about -0.04 В°C, on the back surface of the trunk. Only on front side of shins the temperature increased in non-exchangeable manner, about +0.06 В°C. The important dependence (p<0.05) between the change of temperature in front (r=-0.82) and the back of the trunk (r=-0.78) as well as VO2max was shown. Conclusions: The higher pulse was measured at the studied participant the lower VO2max values were. There is dependence between the thermal reaction and the efficiency - the greater drop of temperature on the trunk the higher VO2max was. Thermal observation can be therefore helpful as indirect estimation of the efficiency in medicine and rehabilitation.